Exchange Rate-Based Stabilization in Western Europe : Greece, Ireland, Italy and Portugal - Detragiache, Enrica; Hamann, A. (Washington, D.C. : International Monetary Fund, 1997)
This paper compares the experience with exchange-rate-based stabilization (ERBS) of four Western European countries with that of high-inflation developing countries. In general, the behavior of key macroeconomic variables-inflation, output, demand, the real exchange rate and the current account-in the four countries examined did not correspond to the pattern observed in developing countries, although some resemblance to this pattern could be found in Italy in 1987-92 and Greece in 1994-96. The experience with ERBS in Western Europe highlights the importance of incomes policy as an ingredient of a successful stabilization program and shows that the adoption of a looser anchor does not necessarily reduce the output cost of disinflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet